The Absence of Color Concept in Pelauw Language (an NSM Approach) - Ahmad Rifani Talaohu; Nurhadi Hamka (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
The notion of colour has been an interesting yet controversial topic especially in the field of linguistics. Some scholars (Berlin and Kay, 1969) argued that every human being should have an insight of the basic colour terms as the universal inventory since the beginning. While other scholar (Wierzbicka, 1996) argued that rather than the colour concept as an inherent nature, it should be a dependant nature in which its terms was emerged because of what have been seen before. This long debate over the colour concept ties to a phenomenon that occurs in one of the indigenous languages in the Eastern part of Indonesia, namely Pelauw. This language apparently does not have any colour terms in its vocabulary as all the words for colour found in this language are borrowed from Bahasa Indonesia. To investigate this strange phenomenon, therefore, this paper will aim to examine the absence of colour concept in Pelauw language, and to use Natural Semantic Metalanguage (NSM) approach (Goddard and Wierzbicka, 2014) for analyzing the terms ‘manggahina’ and ‘mete’ which are somehow used to address white and black colours, respectively. This study uses a qualitative approach with descriptive methods to explain the phenomenon under study using NSM, which in this case, the absence of colour concept in Pelauw language. The results show that colour concept is not something which universally exists to begin with, instead, it is just a result of what have been seen through the vision that visualised and emerged as the colour terms. It is attested through the analysis of terms ‘manggahina’ and ‘mete’ using NSM which concludes that these terms are rather a visual descriptor than a colour concept.